Pengaruh Media Pembelajaran IPS Berbasis Powtoon Terhadap Minat Belajar Siswa Kelas IV SDN Jenggot Krembung Sidoarjo - Prianti, Novita Puspa Dewi; Rezania, Vanda (Jurnal PGSD, 2022)
This study aims to determine the effect of Powtoon-based social studies learning media on the learning interest of fourth-grade students at Jenggot Elementary School, Krembung, Sidoarjo. The type of this research is Pre-Experimental Design which uses One Group Pretest-Posttest Design research design. The sample in this study were 18 students in class fourth-graders at Jenggot Elementary School, Krembung, Sidoarjo. The data collection technique used in this research is a questionnaire/questionnaire. Data on student interest in learning shows the average value (mean) of the pretest is 42.61 while the average value (mean) of the posttest is 70.44. While the tcount value is 10.820 and the ttable value is 2.11991 with a significance value of 0.000 < 0.05. Student interest in learning data shows that tcount 10,820 > ttable 2.11991, this indicates that there is a significant or real difference between pretest learning interest and posttest learning interest, so Ha is accepted or Powtoon-based social studies learning media has a significant effect on fourth-grade students' learning interest, Jenggot Elementary School, Krembung, Sidoarjo.